When Detailed Information Works Better: Comparison of Three- and Five-Color/Letter Front-of-Package Nutrition Labels. Issue 2 (April 2022) - Werle, Carolina O.C.; Pruski Yamim, Amanda; Trendel, Olivier; Roche, Kévin; Nadaud, Perrine
The adoption of front-of-package nutrition labels to promote healthier food choices is increasing worldwide, yet it remains unclear which types of nutrition labels are superior from a public policy perspective. This research compares two common forms of evaluative nutrition labels that vary in the number of colors and corresponding letters they display (three colors, A–C [3C] vs. five colors, A–E [5C]). Four studies, including a field study with vending machines and a study in an experimental supermarket using eye tracking, show that compared with the 3C label and no label (control) conditions, the 5C label enhances purchase intentions and choices of healthy alternatives. In particular, the 5C nutrition label is superior because it provides more information that helps consumers discriminate the products' healthiness. This ability to discriminate healthiness modifies consumers' perceived healthiness of products and influences both their purchase intentions and choice of healthy food options.